Volume Shrinkage of Bone, Brain and Muscle Tissue in Sample Preparation for Micro-CT and Light Sheet Fluorescence Microscopy (LSFM). (25th June 2014) - Buytaert, Jan; Goyens, Jana; De Greef, Daniel; Aerts, Peter; Dirckx, Joris
Abstract: Two methods are especially suited for tomographic imaging with histological detail of macroscopic samples that consist of multiple tissue types (bone, muscle, nerve or fat): Light sheet (based) fluorescence microscopy (LSFM) and micro-computed tomography (micro-CT). Micro-CT requires staining with heavy chemical elements (and thus fixation and sometimes dehydration) in order to make soft tissue imageable when measured alongside denser structures. LSMF requires fixation, decalcification, dehydration, clearing and staining with a fluorescent dye. The specimen preparation of both imaging methods is prone to shrinkage, which is often not mentioned, let alone quantified. In this paper the presence and degree of shrinkage are quantitatively identified for the selected preparation methods/stains. LSFM delivers a volume shrinkage of 17% for bone, 56% for muscle and 62% for brain tissue. The three most popular micro-CT stains (phosphotungstic acid, iodine with potassium iodide, and iodine in absolute ethanol) deliver a volume shrinkage ranging from 10 to 56% for muscle and 27–66% for brain, while bone does not shrink in micro-CT preparation.